Small Molecule with Big Impact: Metarrestin Targets the Perinucleolar Compartment in Cancer Metastasis - Vivek K. Kashyap; Bhuvnesh P. Sharma; Divya Pandey; Ajay K. Singh; Godwin Peasah-Darkwah; Bhupesh Singh; Kuldeep K. Roy; Murali M. Yallapu; Subhash C. Chauhan (Cells)
Metarrestin (ML246) is a first-in-class pyrrole–pyrimidine-derived small molecule that selectively targets the perinucleolar compartment (PNC). PNC is a distinct subnuclear structure predominantly found in solid tumor cells. The occurrence of PNC demonstrates a positive correlation with malignancy, serving as an indicator of tumor aggressiveness, progression, and metastasis. Various promising preclinical results have led to the clinical translation of metarrestin into a first-in-human trial. This review aims to summarize (i) the current understanding of the structure and function of PNC and its role in cancer progression and metastasis, (ii) key findings from studies examining the effect of metarrestin on various cancers across the translational spectrum, including in vitro, in vivo, and human clinical trial studies, and (iii) the pharmaceutical relevance of metarrestin as a promising anticancer candidate. Furthermore, our molecular docking and MD simulation studies show that metarrestin binds to eEF1A1 and eEF1A2 with a strong and stable affinity and inhibits eEF1A2 more efficiently compared to eEF1A1. The promising results from preclinical studies suggest that metarrestin has the potential to revolutionize the treatment of cancer, heralding a paradigm shift in its therapeutic management.